Heavy metals in soil from urban areas of Klang, Malaysia, and their health risk assessment using in vitro digestion method - Yuswir, Nurul Syazani (2015)
Background: Klang District is considered as one of the area that undergoes a rapid urbanization and surrounded by land and sea based anthropogenic activities. These anthropogenic activities have given various impacts on environmental and human health. Objective: Thus, the aim of this study was to determine the total and bioavailable of heavy metal concentrations (Al, Fe, Zn, Cu, Co, Cd, Pb and Cr) in urban surface soil samples. In addition, this study also aimed to determine possible sources in Klang District urban surface soil using multivariate analysis. Besides, this study also aimed to determine health risks posed by bioavailable of heavy metal in urban soil on adult and children. Methodology: A total of 76 urban soils in Klang District have been sampled and analyzed for total and bioavailable of heavy metal concentrations (Al, Fe, Zn, Cu, Co, Cd, Pb and Cr) using Inductively Coupled Plasma-Optical Emission Spectrometry. Total heavy metal concentration was determined using aqua regia digestion method while bioavailable of heavy metal concentration was determined using Physiologically Based Extraction Test (PBET) in vitro digestion method. Result: Results showed that the bioavailable of heavy metal concentrations were in the order of Al (25 mg/kg), Fe (6.7 mg/kg), Zn (5.6 mg/kg), Cu (3.0 mg/kg), Co (0.22 mg/kg), Cd (0.14 mg/kg), Pb (0.11 mg/kg) and Cr (0.10 mg/kg), while concentration of total heavy metal were in the order of Fe (9090 mg/kg), Al (6171 mg/kg), Cu (294 mg/kg), Zn (276 mg/kg), Pb (53 mg/kg), Cr (16 mg/kg), Co (1.2 mg/kg) and Cd (0.71 mg/kg). From the Spearman correlation coefficient (r) value, significant correlation were observed for Al-Fe (r = 0.681), Cd-Co (r = 0.495), Cu-Zn (r = 0.232), Fe-Pb (r = 0.260), Fe-Zn (r = 0.239), Al-Cu (r = -0.503), Co-Pb (r = -0.241) and Cu-Fe (r = -0.492). Spearman correlation output showed that heavy metal such as Al and Fe may come from natural sources while heavy metal such as Cd, Co, Cr and Cu may come from anthropogenic sources. Cluster Analysis output showed that these heavy metals can be classified into four clusters namely Cluster 1 which consisted of Cd, Cr, Co and Pb, Cluster 2 consisted of Zn and Cu, Cluster 3 consisted of Fe and Cluster 4 consisted of Al. For Clusters 1 and 2, anthropogenic activities were believed as the sources while for Clusters 3 and 4, the heavy metals originated from natural sources. For the health risks, the results of Hazard Quotient and Total Risk showed that heavy metal contamination via soil ingestion pathway in Klang District may not pose carcinogenic and non-carcinogenic risk to human adult, but it may pose carcinogenic and non-carcinogenic risks to children. Conclusion: Output from this study can be used to fill the knowledge gap on effect of heavy metal and potential health risks due to heavy metal exposure in urban area especially in Malaysia.